GAMBARAN HAZARD KERJA PADA PERAWAT DI SMC RS TELOGOREJO - Siti Mukaromah; Prita Adisty Handayani; Laura Khattrine Noviyanti (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2023)
The hospital environment has the potential for disease transmission, nurses as implementing nursing care are at risk of contracting infectious diseases in carrying out their duties. In hospitals, there are occupational hazards including biological hazards, chemical hazards, ergonomic hazards, physical hazards, and psychosocial hazards. The purpose of this study was to describe the occupational hazard of nurses at SMC RS Telogorejo. This research is a descriptive survey by conducting observations and interviews, the technique of determining the sample is non-probability sampling, the type of purposive sampling with a large sample of 228 respondents. The results of this study illustrate that the majority of nurses have exposure to physical work hazards (cold climate), biological work hazards (airborne), chemical hazards (use of disinfectant liquids and handscoons), ergonomic work hazards (medical measures), and psychosocial work hazards (workload). From this study it was found that overall, nurses at SMC RS Telogorejo were exposed to occupational hazards in the mild category. It is expected that the SMC RS Telogorejo will monitor and evaluate the implementation of K3RS for nurses in carrying out their duties and responsibilities so as to improve the performance, safety and health of nurses.